REGENERATION OF AMMONIA SOLUTION FOR CO2 CAPTURE IN POSTCOMBUSTION - CAROL TORO; CHAKIB BOUALLOU (Scientific Study & Research: Chemistry & Chemical Engineering, Biotechnology, Food Industry)
This study investigated enthalpy of solutions and solubility for a NH3/CO2 system. Measurements were performed in a thermoregulated Lewis-type cell reactor, temperatures ranging from 278 to 303 K and mass concentrations from 2 wt% to 5 wt%. Enthalpies of solution of CO2 and solubility have been obtained as function of loading, α (moles CO2/mol NH3). Results show that ammonia solutions concentrations of 3 and 5 wt% promote the formation of ammonium bicarbonate. Beside, ammonia concentration of 2 wt% promotes the formation of ammonium carbonate. Therefore, to use ammonia concentrations of 3 and 5 wt% need less energy that a concentration of 2 wt% to reverse the reaction. Regeneration system was simulated using Aspen plus™ software for a pulverised coal fired power plant (CF) in a post-combustion process. Model analysis established that NH3 heat duty is lower than MEA and MDEA ones. The energy consumption reaches 2.83 GJ•t-1 CO2. Regarding heat duty and ammonia losses, 3 wt% NH3 is the suitable concentration to capture CO2.